Evaluation of Biological Activities of Evolvulus Nummularius L. through Insecticidal, Insect Repellency and Brine Shrimp Lethality Tests - Moniruzzaman, Md; Parvin, Nayeema; Sultana, Sabina; Abdullah, Mohammad; Khan, Ataur Rahman; Islam, Nurul (Journal of Life and Earth Science, 2014)
Assessment of Evolvulus nummularius L. through whole plant extracts (collected in petroleum ether [Pet.E.], chloroform [CHCl3] and methanol [MeOH]) were made against Tribolium castaneum (Hbst.) for insecticidal and insect repellency and against Artemia salina L. for brine shrimp lethality, and the results were promising. The LC50 values against T. castaneum adults for Pet.E. extract were 1.280, 1.220, 1.096 and 1.030?g cm-2; for CHCl3 extract 3.249, 2.990, 2.526 and 2.204?g cm-2; and for MeOH extract 2.925, 1.899, 1.875 and 1.789?g cm-2, respectively for 12, 24, 36 and 48h of exposure. The intensity of activity could be arranged in a descending order: Pet.E. extract> MeOH extract> CHCl3 extract. For repellency, CHCl3 and MeOH extracts offered moderate activity (P <0.01), but the Pet.E. extract did not show efficacy against the beetles. The same extracts responded positively in brine shrimp lethality assay where the LC50 values for Pet.E. extract were 141.553, 98.941, 24.684 and 8.560ppm; for CHCl3 extracts 699.048, 366.663, 326.0039 and 40.114ppm; and for MeOH extracts 2336.982, 1258.605, 355.962 and 137.0589ppm respectively for 12, 18, 24 and 30h of exposure. However, the intensity of activity could be arranged in a descending order: Pet.E. extract> CHCl3 extract> MeOH extract. DOI: http://dx.doi.org/10.3329/jles.v8i0.20153 J. Life Earth Sci., Vol. 8: 101-104, 2013